Poised Between Order and Conflict: What Future for the Smart City? - Gurashi, Romina (SocietàMutamentoPolitica, 2023)
The aim of this study is to reflect on how the longstanding contradiction between order and conflict in urban contexts is now articulated in the context of smart cities. Apparently, smart cities are the best place to live in order to enjoy greater capacity for choice, self-determination, well-being and independence. But is this really the case? Are smart cities and their technological drift towards increasingly wider spaces of order and control really able to guarantee wide spaces of freedom? What role does or can conflict play? Through the analysis of various case studies (Qatar, China and Ukraine), we will try to improve our understanding of the dichotomous relationship between order and conflict both from an internal perspective within the city and from an external perspective (i.e. when attacks from outside occur). The study will proceed through a preliminary analysis of the state of the art on the smart city literature in order to grasp what are the “promises” that this model of development brings with it and the criticalities connected to its development. At a later stage, we will proceed to focus on issues related to the problems of social order and conflict both from an internal and external perspective.